2014
DOI: 10.1186/s12939-014-0083-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with unhealthy behaviours and health outcomes: a cross-sectional study among tuscan adolescents (Italy)

Abstract: BackgroundWe aimed to determine the extent to which three core variables (school environment, peer group and family affluence) were associated with unhealthy behaviours and health outcomes among Tuscan adolescents. The unhealthy behaviours considered were smoking, alcohol consumption, sedentary lifestyle and irregular breakfast consumption; health outcomes were classified as self-reported health, multiple health complaints and life satisfaction. School environment was measured in terms of liking school, school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 29 publications
1
18
0
10
Order By: Relevance
“…Several studies have found a positive association between breakfast skipping and overweight in both genders [6,13,37,40,41,49,50]. In addition, a significant dose-response relationship between breakfast skipping and overweight was observed in Indian adolescents [37].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several studies have found a positive association between breakfast skipping and overweight in both genders [6,13,37,40,41,49,50]. In addition, a significant dose-response relationship between breakfast skipping and overweight was observed in Indian adolescents [37].…”
Section: Discussionmentioning
confidence: 93%
“…One possible explanation for this relationship may be dissatisfaction with body image and the intention to lose weight due to media pressure and desire for thinness [32,41]. On the other hand, some authors [37,42], found no gender difference in breakfast skipping prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Uwarunkowaniem społeczno-ekonomicznym najczęściej wymienianym w ujętych publikacjach był status socjoekonomiczny. Wśród miar, według których szacowano SES, znalazły się: skala zasobów materialnych rodziny (Lazzeri et al 2014), uprawnienie do pobierania darmowych posiłków (Farmer, Hanratty 2012), profesja ojca (Thibault et al 2009), wykształce-nie rodziców (Ferreira et al 2006), status zawodowy rodziców (Haug et al 2006), pozycja społeczna rodzica o wyższym stanowisku (Raudsepp, Viira 2000), wykształcenie matki (Gordon-Larsen et al 2000) i dochód rodziny (Ferreira et al 2006;Haug et al 2006;Raudsepp, Viira 2000;Gordon-Larsen et al 2000).…”
Section: Wynikiunclassified
“…Środowisko szkolne, które było drugą ze zmiennych determinujących zachowania zdrowotne, określano przez: stosunek do szkoły, wsparcie rówieśni-cze, osiągnięcia szkolne (Lazzeri et al 2014), postrzeganie szkoły jako wspierają-cego środowiska , relacje rodziców i dzieci ze szkołą ) oraz poczucie przynależności do szkolnej społeczności (Brooks et al 2012). …”
Section: Wynikiunclassified
See 1 more Smart Citation